Sistema silvipastoril no Oeste Paranaense com Jatropha curcas L. e tifton 85 - Schulz, Deisinara Giane (2011)
The establishment of silvipastore systems for small farmers tends to improve productivity with great potential for economic and environmental gains. The consortium between physic nut and Tifton 85 can be an alternative for system implementation. This study aimed to evaluate the development of Jatropha curcas L. in relation growth space through modeling suggested by Nelder (1962) in consortium with or without the herbaceous Tifton 85. The experiment was conducted at the Experimental Station of Pato Bragado, which belongs to the Center for Experimental Stations of the Western Paraná State University, Campus of Marechal Cândido Rondon. The planting system used was composed of two Nelter plots with four spacing plant (1,53, 3,06, 4,59 and 6,12 meters) with eight replicates associated or not with the herbaceous Tifton 85. The spacing used was 2 m between plants, comprising ten meter radius separed by an angle of 45° to each other. The experiment was conducted according to a completely randomized design with split parcel in time, with two plots, which were the parcel of space of planting, split parcel, the time of evaluation, carrying out joint analysis of experiments with and without Tifton 85. Data were subjected to analysis of variance and polynomial regression of the 5% significance. Chemical analysis of sheets was carried out analysis of variance in a 2x4 factorial design, two factors are considered as systems of cultivation in four planting spaces in experimental cazualizado with four replicates per plant space. Means were compared by Tukey test (p<0.05) through genes software. For the analysis of herbal Tifton 85 was applied to the completely randomized experimental design in a split parcel in time, with three replicates for the evaluation of height, fresh and dry weight of plants, and nine repetitions for bromatological variables. The cultivation of physic nut in the spacing of 1,53 meters implies greater competition between plants in both the planting as a single and consortium, with lower values for planting trees in the consortium. The cultivation of physic nut single spaced 4,5 meters implies less competition between plants. The composition of Tifton 85 chemical presented characteristics of good quality and quantity for fodder production in intercropping with J. curcas, limited to the spacing of 2x1,53 and 2x3,03 feet between the physic nut plants.